Determinants of self-reported sexually transmitted infections among reproductive age women in Senegal: evidenced by Senegal demographic and health survey - Beletu Kinfe; Habtemariam Mulugeta Abate; Gosa Mankelkl (BMC, 2024)
Abstract Background Globally, access to sexual and reproductive health is a significant public health issue for women of the reproductive age group. Senegal is a low-income country with limited access to reproductive health services, such as in the prevention and treatment of STIs. The prevention and treatment of STIs is one of the goals set by the government to decrease reproductive health-related morbidity and mortality among women. So, the main objective of this research was to evaluate the prevalence's and determinant of self-reported sexually transmitted infections among reproductive-age women. Methods Data from the 2023 Senegal Demographic and Health Survey datasets were used for secondary data analysis. A total of 16,583 women of reproductive age participated in the study. Bivariate analysis was employed in order to select the factors for multivariate analysis. In the multivariate analysis, variables with p < 0.05 significance levels were considered to be significant predictors of sexually transmitted infections among reproductive-age women. Finally, the percentage and odd ratio, together with their 95% confidence intervals, were reported. Results The prevalence of sexually transmitted infection among women was 3.21% with a 95 CI. [2.95-3.49] in the last 12 months. Being between the age range of 20 and 44 years old; attending higher education [AOR: 2.70, 95% CI (1.74, 4.19); P = 0.0001]; women who were never in union [AOR: 0.09, 95% CI (0.046, 0.17); P = 0.001] were positively associated with sexually transmitted infections among women. In contrast to this, living in Louga [AOR: 0.41, 95% CI (0.23,0.69); P = 0.001]; Fatick [AOR: 0.33, 95% CI (0.18,0.61); P = 0.0001]; Kolda [AOR: 0.23, 95% CI (0.11,0.49); P = 0.0001]; Kedougou [AOR: 0.34, 95% CI (0.17,0.68); P = 0.002]; and Sedhiou [AOR: 0.43, 95% CI (0.23,0.79); P = 0.007] and women who had history terminated pregnancy [AOR: 1.27, 95% CI (1.03,1.58); P = 0.023] were negatively associated with sexually transmitted infections among women. Conclusions and recommendations Women's sexually transmitted infection has been associated with sociodemographic and geographic determinants such as the age of the woman, region, educational status, marital status, and history of terminated pregnancy. Therefore, to prevent the spread of sexually transmitted infections among women, the governments of Senegal and other concerned stakeholders should give special attention to women by addressing sociodemographic and geographic determinants.